Inequality Aversion and Performance in and on the Field - Benno Torgler; Markus Schaffner; Bruno S. Frey; Sascha L. Schmidt; Uwe Dulleck (Center for Research in Economics, Management and the Arts (CREMA), 2008)
The experimental literature and studies using survey data have established that people care a great deal about their relative economic position and not solely, as standard economic theory assumes, about their absolute economic position. Individuals are concerned about social comparisons. However, behavioral evidence in the field is rare. This paper provides an empirical analysis, testing the model of inequality aversion using two unique panel data sets for basketball and soccer players. We find support that the concept of inequality aversion helps to understand how the relative income situation affects performance in a real competitive environment with real tasks and real incentives.
Keywords: D00; D60; L83; 330; Inequality aversion; relative income; positional concerns; envy; social comparison; performance; interdependent preferences